فاعلية وحدة مطورة في ضوء متطلبات التنور العلمي والتقني في تدريس العلوم في تنمية الثقافة العلمية وتحصيل المعرفة العلمية لدى طالبات الصف الثالث المتوسط - عسيري، أسماء بنت عبدالرحمن آل منير (الجامعة الإسلامية بالمدينة المنورة, 2022)
هدف البحث إلى تعرف فاعلية وحدة مطورة في ضوء متطلبات التنور العلمي والتقني في تدريس العلوم في تنمية الثقافة العلمية وتحصيل المعرفة العلمية لدى طالبات الصف الثالث المتوسط، ولتحقيق هذا الهدف تم استخدام المنهج التجريبي ذي تصميم القياسين القبلي والبعدي للمجموعتين الضابطة والتجريبية، وتم اختيار عينة البحث من طالبات الصف الثالث المتوسط في المدرسة المتوسطة (٤٠) بالمدينة المنورة، تم تقسيمهن إلى مجموعتين تجريبية بلغ عددهن (٤١) طالبة، وضابطة بلغ عددهن (٤١) طالبة، طبق عليهن الأداتين التاليتين: اختبار الثقافة العلمية، واختبار تحصيل المعرفة العلمية قبليا وبعديا، وقد توصلت النتائج إلى: أن متطلبات التنور العلمي والتقني اللازمة لتدريس العلوم في المرحلة المتوسطة هي: متطلبات معرفية اشتملت (5) متطلبات فرعية، ومتطلبات مهارية اشتملت (٦) متطلبات فرعية، ومتطلبات اجتماعية اشتملت (5) متطلبات فرعية، كما أظهرت النتائج تدني متوسط درجات الطالبات في الثقافة العلمية وتحصيل المعرفة العلمية وذلك لكل من المجموعة التجريبية والضابطة، توجد فرق ذو دلالة إحصائية عند مستوى الدلالة (0.05) بين متوسطي درجات المجموعة التجريبية والضابطة في التطبيق البعدي لاختباري الثقافة العلمية وتحصيل المعرفة العلمية لصالح المجموعة التجريبية، ووجود أثر وفاعلية كبير لتدريس وحدة مطورة في ضوء متطلبات التنور العلمي والتقني في تدريس العلوم لتنمية الثقافة العلمية وتحصيل المعرفة العلمية لدى طالبات الصف الثالث المتوسط. The aim of the research is to know the effectiveness of a developed unit in the light of the requirements of scientific and technical enlightenment in teaching science in developing scientific culture and the acquisition of scientific knowledge for third grade intermediate students. To achieve this goal, the experimental method was used with the design of the pre and post measurements for the control and experimental groups. The research sample was selected from the third intermediate grade students in the middle school (40) in Madinah. They were divided into two experimental groups whose number was (41) students, and the control group numbered (41). A female student. The following two tools were applied to the two groups: the scientific culture test, and the scientific knowledge acquisition test, before and after. The results concluded: that the scientific and technical enlightenment requirements necessary for teaching science in the intermediate stage are: knowledge requirements that included (5) sub-requirements, skill requirements that included (6) sub-requirements, and social requirements that included (5) sub-requirements. The results showed low average scores of female students in scientific culture and acquisition of scientific knowledge for both the experimental and control group. There is a statistically significant difference at the significance level (0.05) between the mean scores of the experimental and control group in the post application of the scientific culture and scientific knowledge acquisition tests in favor of the experimental group. There is a significant impact and effectiveness of teaching a developed unit in light of the requirements of scientific and technical enlightenment in teaching science to develop scientific culture and the acquisition of scientific knowledge for third-grade intermediate students.
Keywords: العملية التعليمية -- العلوم المعرفية -- المناهج الدراسية -- الاستراتيجيات التدريسية -- مادة العلوم -- طلبة المرحلة المتوسطة -- المعرفة النافعة -- التقنيات الحديثة